The sequence at Carihuela Cave and its potential for research into Neanderthal ecology and the Mousterian in southern Spain. (1st August 2019) - Carrión, J.S.; Fernández, S.; Jiménez-Arenas, J.M.; Munuera, M.; Ochando, J.; Amorós, G.; Ponce de León, M.; Zollikofer, C.; Martín-Lerma, I.; Toro-Moyano, I.; Hajdas, I.; Walker, M.J.
Abstract: Hitherto unpublished 14 C and 230 Th 234 U determinations from Carihuela Cave (Granada province, Andalusia, Spain) raise a possibility of late survival here of Neanderthals and their Mousterian technocomplex into an advanced stage of the Late Pleistocene (MIS-3), when anatomically-modern humans with Upper Palaeolithic toolkits were penetrating the region, and when also several carnivore taxa competed for access to the cave. Previous palaeopalynological studies are reinforced by new pollen analyses of samples extracted from coprolites. The palaeoecological and sedimentological records bear comparison with new data from the Padul peat deposits in the Sierra Nevada, and are in line with the view that there was late persistence of the Mousterian in Granada. There is a pressing need for renewed international multidisciplinary research at Carihuela Cave, with up-to-date lithostratigraphical and dating techniques that can expand on results obtained from fieldwork undertaken by a previous generation of researchers. Carihuela Cave continues to hold out great promise for analysing Neanderthal palaeoecology during the Late Pleistocene up to the appearance in southeastern Iberian Peninsula of anatomically-modern Upper Palaeolithic people, particularly with regard to the earlier phases of the Middle Palaeolithic at the cave which await intensive excavation but apparently extend back in time to the last interglacial period. Highlights: New dating is provided for the Neanderthal site of Carihuela Cave. The survival of Mousterian until the end of the MIS 3, is suggested. Pollen analyses of carnivore coprolites dated from 23.4 to 31.0 ka. The Carihuela sequence accords well with palynological findings from Padul.